DUE TO LEGAL POSITION AND LEGAL SURROGACY AGREEMENT AS AN INNOMINAAT AGREEMENT IN THE PERPECTIVE OF CIVIL LAW, ISLAMIC LAW AND NATIONAL LAW - Peni Rinda (Jurnal Pembaharuan Hukum, 2019)
Technological developments in medicine have provided an outlet for community issues with the discovery of a new method of artificial insemination is known as in vitro fertilitization (IVF). For couples who want to have children but due to medical reasons can not obtain offspring naturally, with IVF method can obtain offspring / children. But in its development appears IVF lease term or the surrogate mother's womb, the sperm and ovum from a legitimate married another woman entered in the womb. Therefore the aim of this study to determine the legal position of surrogacy agreement as an innominaat agreement in the perspective of civil law, Islamic law national law, This research used normative juridical approach, descriptive analytical research specification, method of data collection is done with a literature study on legal materials, both primary legal materials, as well as secondary materials, then analyzed by qualitative descriptive. The results showed that a good legal position surrogacy agreement according to the Civil Law, Islamic law and national law is as the agreement is not named (innominaat) and surrogacy agreement is not allowed or unlawful. While the legal consequences of surrogacy agreements either under Civil Law, Islamic law, and national law relating to the status of children, descent problems, inheritance and other rights. The legal status of children under civil law can be a legitimate child of the surrogate mother, it could be a child outside of mating recognized, while according to Islamic law status of the child as a child of the uterus rental yields laqith, while according to national law, the legal status of the child as a foster child. This inheritance rights issue depends the legal status of the child, there is nothing not inherit (civil relationship with his mother).